Fattening practices of beef cattle for quality meat production at Rangpur district of Bangladesh - Hasan, MM; Hashem, MA; Azad, MAK; Billah, MM; MM Rahman (Meat Research, 2022)
The study was aimed to assess the ongoing beef cattle fattening practices at some selected areas of Rangpur district of Bangladesh. The survey was carried out through a structured questionnaire among 45 selected farmers during February to June, 2020. Parameters studied were the roughage and concentrate feeding practices, treatment of straw or green grass, ration formulation, introduction of steroids for fattening, cost return analysis of cattle fattening practices. It was found from the study that the respondents were About 55.55% farmers used own capital for fattening, while 33.33, 6.67 and 4.44% farmers got money from NGO, other people and bank loan respectively. Most of the farmers (44.44%) reared indigenous bulls compared to crossbred (24.44%) and mixture of both (31.11%). A significant number of farmers reared uncastrated bulls (88.89%) and nobody reared cows or heifers for fattening. Majority of the farmers’ fattened cattle only before Eid-ul-Adha (57.78%) and only 24.48% farmer fattened cattle round the year and the rest of the farmers practiced seasonal fattening. Majority of the farmers supplied roadside grass (55.56%) as the source of forages compared to straw (17.78%) and cultivated fodder (26.67%). In case of concentrate feeding, only 20% farmers supplied commercial pellet feed, 35.56% supplied local hand mixed feed and 44.44% supplied both pellet and hand mix feed. Among the cattle fattened farmers only 5% farmers administered steroids as a growth promoter and 95% of them did not use any kinds of growth promoter at the period of fattening. Therefore, beef would be safe for human consumption without any health hazard.